Mountains of the pharaohs the untold story of the pyramid builders - Hawass, Zahi A. 1947- (Doubleday, 2006)
Examines the construction of the great pyramids of Giza, the saga of the fourth dynasty of Egypt's Old Kingdom, and the advanced civilization that spawned the engineering expertise and architectural artistry that existed during the time.
Keywords: Geschichte; Pyramids of Giza (Egypt); Egypt -- History -- Old Kingdom, ca. 2686-ca. 2181 B.C